ANALYSIS OF THE APPLICATION OF ADVOCATE SUCCESS FEES IN HANDLING INHERITANCE DISPUTE CASES ACCORDING TO THE THEORY OF AL- JI'ALAH - Haris Munandar; Saifuddin Sa'dan (JURISTA: Jurnal Hukum dan Keadilan, 2025)
An advocate is a person whose profession is to provide legal services to the public, both inside and outside the court. The types of advocate honorarium can generally be divided into 3 (three) types, namely lawyer fees, operational fees, and success fees. Legally, the application of success fees in the process of handling cases or providing legal services by advocates is not regulated in legislation. In practice, the success fee is requested by the advocate to the client as a form of reward for the advocate's victory. The research method used is a qualitative research method with an analytical descriptive approach, data collection techniques are carried out by interviews and documentation as well as literature studies and regulations related to this research. The results showed that the success fee practice carried out by advocates at the IM and Partners Law Office went through a series of processes starting from the agreement stage of determining the percentage of the success fee between the client and the advocate and signing the advocate's legal services. In practice, success fee payments are not only paid in cash, but also in the form of payments in the form of movable or immovable objects. The application of the amount of the success fee by the advocate at the IM and Partners Law Office is in accordance with the concept of the ji'alah contract, the success fee received by the advocate in handling the inheritance dispute case is a form of client reward for the advocate for helping to resolve the client's legal problems.